PENYISIHAN MERKURI DAN BESI DARI AIR SUNGAI MENGGUNAKAN BUBUK CANGKANG TELUR (Mercury and Iron Removal from River Water Using Eggshell Powder) - Badariah; Syahran; Sarah Fiebrina Heraningsih (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2023)
Mercury and iron are toxic heavy metals that often enter the waters through anthropogenic activities. The Batanghari River is one of the rivers affected by heavy metals. This study aims to remove mercury and iron from river water by using an adsorbent from egg shells. The treatment used was direct contact through stirring with variations of 45 minutes, 90 minutes, and 135 minutes. The doses of eggshell powder used were 1 grams, 5 grams, 10 grams, and 15 grams. The optimal removal efficiency is 100% for mercury and 89.54% for iron. The best adsorbent dose is 5 grams for mercury and 10 grams for iron and the best stirring speed is 135 minutes on both types of metals. The results of this study found that the removal of mercury and iron using eggshell powder is an easy, cheap, and effective process to implement.